5h=3h+12

Simple and best practice solution for 5h=3h+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5h=3h+12 equation:


Simplifying
5h = 3h + 12

Reorder the terms:
5h = 12 + 3h

Solving
5h = 12 + 3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-3h' to each side of the equation.
5h + -3h = 12 + 3h + -3h

Combine like terms: 5h + -3h = 2h
2h = 12 + 3h + -3h

Combine like terms: 3h + -3h = 0
2h = 12 + 0
2h = 12

Divide each side by '2'.
h = 6

Simplifying
h = 6

See similar equations:

| 6.5/9 | | 2x+10x-9+2x-7=180 | | 5(w-3)-3=-7(-3w+2)-2w | | (4-v)(4v+2)=0 | | 1+3x=-17-3x | | 18+6a=6 | | -27z-0.6=-37z+2.8 | | 6+78x=52x+12 | | 2x+18-7x^2+3x-9= | | 6x-4=X+2 | | 33=24+v | | 10n-150=9 | | -27=-6x+3(x-3) | | x-2=2x-17 | | y=0.5x+70 | | x(x+3)-(x-2)2=10 | | 27-4x=-5 | | lnx^2-4lnx=12 | | (2x+3)-(x-1)=0 | | 2x+70=150 | | ln^2-4lnx=12 | | 16x^2+9x^2=6400 | | x/3=3/999 | | x/3=3/x | | 3x-1-(2x-1)=0 | | 70=30q | | ((-x^6)/999)=519086/-987320946 | | 4(x-1)-8(x+1)=4(x+3) | | 0=x^4-50 | | 3/2.50*15=x | | 200x=300y | | -x-5=-a |

Equations solver categories